Correlation between catch method, condition, and diet patterns in Atlantic cod (Gadus morhua). (8th September 2019) - Ljungberg, Peter; Ovegård, Maria; Öhman, Kristin; Königson, Sara
Abstract: With seal populations increasing significantly in the Baltic Sea, the conflict between seals and fisheries is growing. The most sustainable method for mitigating the seal–fishery conflict is to develop and use seal-safe fishing gear. Although pots have been shown to be a promising alternative to gillnets for catching cod ( Gadus morhua ), there are indications that cod caught in pots are in poorer condition than those caught in gillnets, potentially making the pots a less-economical alternative. This study investigates whether this difference in condition is consistent over larger spatial scales. Gear-specific cod condition was related to both short-term (determined from stomach contents) and long-term (determined by stable isotope analysis) diet composition. Results indicate that differences in fish condition between gear types are consistent over large areas, possibly due to temporal and spatial differences in feeding strategies. We argue that condition differences between pot- and gillnet-caught cod may be driven by differences in behavioural traits. Consequently, fishing with a certain gear type may have ecological consequences affecting population characteristics, with implications for fisheries management. From the perspective of the seal–fisheries conflict, pots may ultimately have consequences on the catch value of fish.